Taxation of automation and artificial intelligence as a tool of labour policy - OOI, Vincent (Institutional Knowledge at Singapore Management University, 2019)
Rapid developments in automation technology pose a risk of massdisplacement of human labour, resulting in the need to support and retraindisplaced workers (a negative externality). We propose an “automation tax”that would slow the adoption of automation technology in appropriatecircumstances, giving workers and social support systems time to adapt. Thiscould be easily implemented through changes to the existing schedular systemof depreciation/ capital allowances, reducing the uncertainty of its applicationand implementation costs. Such a system would be flexible enough to keepup with rapid technological developments. Two main dimensions may beadjusted to produce intended distortionary effects: 1) accelerated depreciation,and 2) bonus depreciation. While the benefits of efficiency gains mean thatthe automation tax is unlikely to have widespread application, it does providea useful tool for specific situations where the rate of automation needs to beslowed due to its resultant social costs.